Cyclooxygenase-2 expression and its association with vascular endothelial growth factor, microvessel density and clinicopathologic characteristics of colorectal carcinoma - Qin, Zhao-Yang; Guo, Xiao-Yan; Xu, Jing-Zhong; Wang, Gang-Ping (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to investigate the expression of cyclooxygenase type-2 (COX-2) and its association with angiogenesis and clinicopathologic characteristics of colorectal carcinoma (CRC). COX-2 expression was detected by means of immunohistochemistry in a series of human tissue samples with CRC (n = 120), dysplasia tissue closely adjacent to carcinomas (n = 40) and normal colorectal mucosa (n = 40), and their expressions association with vascular endothelial growth factor (VEGF), CD31-labeled micorvessel density(MVD) in CRC and other clinicopathologic characteristics were investigated. The expression of COX-2 in CRC tissues (78.3%) was obviously higher than that in adjacent tissue and normal mucosal tissue (p<0.01). COX-2 expression was correlated significantly with the grading, advanced cancer, Dukes stage and lymph node metastasis, distant metastasis and VEGF (p<0.05). Our result demonstrates that COX-2 expression was significantly higher in earlier stages of CRC. It can be suggested that COX-2 expression may be important in the initial development of CRC. The findings of the present study suggest that COX-2 overexpression in CRC may be considered as a negative prognostic marker.